Unauthorised access : physical penetration testing for IT security teams - Allsopp, Wil. (Chichester, England : Wiley, 2009)
"Featuring a Foreword written by world-renowned hacker Kevin D. Mitnick and lead author of The Art of Intrusion and The Art of Deception, this book is the first guide to planning and performing a physical penetration test. Inside, IT security expert Wil Allsopp guides you through the entire process from gathering intelligence, getting inside, dealing with threats, staying hidden (often in plain sight), and getting access to networks and data"--Resource description page.
1. Basics of Physical Penetration Testing -- 2. Planning Your Physical Penetration Tests -- 3. Executing Tests -- 4. Introduction to Social Engineering Techniques -- 5. Lock Picking -- 6. Information Gathering -- 7. Hacking Wireless Equipment -- 8. Gathering the Right Equipment -- 9. Tales from the Front Line -- 10. Introducing Security Policy Concepts -- 11. Counter Intelligence -- Appendix A. UK law -- Appendix B. US law -- Appendix C. EU law -- Appendix D. Security Clearances -- Appendix E. Security Accreditations.
Includes index.
Keywords: COMPUTER SECURITY -- TESTING